On the rules for developing working land management projects to improve the condition of agricultural land - Koshel, A.; Kolhanova, I.; Kempa, O.; Stacherzak, A. (Land Management, Cadastre and Land Monitoring, 2024)
Abstract. The article proposes scientific and methodological approaches to the development of measures to improve the condition of agricultural land in modern land management documentation. The main focus is on agroecological, agrochemical and agrotechnical approaches aimed at ensuring sustainable development of the agricultural sector. The agroecological approach includes soil assessment, biodiversity conservation and rational use of water resources. The agrochemical approach involves soil analysis, rational fertilisation and the use of organic fertilisers to improve soil structure. The agrotechnical approach focuses on the use of conservation technologies, crop rotation and erosion protection measures. The integration of these approaches allows for a comprehensive approach to improving the condition of agricultural land, which contributes to increased productivity and conservation of natural resources. The article offers practical recommendations for farmers and agronomists interested in the sustainable development of the agricultural sector. Key words: protection of agricultural land, land management, improvement of agricultural land, land management, land management documentation